The Influence of Powtoon and Reading Habits toward Students’ Reading Comprehension Achievement at SMK Utama Bakti Palembang: English - Dicky Andrian; Mulyadi; Masagus Firdaus (Prodi Tadris Bahasa Inggris, 2024)
This research aimed to investigate the influence of Powtoon usage and reading habits on students' reading comprehension achievement at SMK Utama Bakti Palembang. This research was conducted using Factorial Design as an experimental method. The study encompassed a population of 209 students, with a sample size of 56 students, and employed a factorial design methodology. The findings revealed that the utilization of Powtoon positively impacted students' reading comprehension skills, regardless of their reading habits, be it high or low. Furthermore, reading habits demonstrated a significant effect on students' reading achievement, with those having high reading habits exhibiting superior reading comprehension compared to their low-reading habit counterparts, irrespective of Powtoon usage. This research contributes valuable insights into the dynamic interaction between Powtoon implementation and reading habits in molding students' reading abilities, thus carrying potential implications for teachers and curriculum designers in enhancing the quality of learning and providing adequate support to enhance students' reading proficiency.